Pengolahan Inovasi Bandeng Modern Kaya Protein dengan Pemanfaatan Sumberdaya Lokal Jawa Timur dan Pemberdayaan Masyarakat - Ma’arif, Achmat Samsul; Wati, Ristia Emalia; Septyarini, Marsya Cahya; Rahman, Prasstyo Aditya; Dressanala, Kinaryosih; Radianto, Denny Oktavina (Sci-tech Journal, 2023)
The main reason people are still reluctant to eat or process milkfish is the large number of spines that are difficult to clean, this reduces their interest in eating milkfish. In this era of globalization, the entry of foreign cultures into Indonesia has had an impact on lifestyles and eating patterns as well as people's culture giving rise to many kinds of food that are unique, practical but still nutritious enough. From the circumstances and opportunities we try to solve social problems while simultaneously wanting to access large market opportunities. This study uses quantitative methods based on systematic facts or characteristics of certain populations factually and carefully. We have created a product that is liked by various groups and utilize social media to attract enthusiasts. Looking at cities in Indonesia where the density is dominated by youth, they are the biggest contributors to urban development in all sectors. The two conditions above are what underlies the birth of this Milkfish Mci business, namely by producing modern processed milkfish products and utilizing social media to attract youth. With the existence of processed milkfish products that are in accordance with the interests of the target market. Because milkfish contains higher nutrition, it is of interest to the general public. For transactions that themselves use the method commonly used by the public. Marketing information uses media that is often found by the target market with the online platform services available in today's digital era. Especially milkfish which is abundant in the East Java area. Keywords: Processing, milkfish, milkfish innovation, milkfish Mci business, processed milkfish products.